1995
DOI: 10.1007/s001250050378
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatic secretion of very-low-density lipoprotein apolipoprotein B-100 in NIDDM

Abstract: We measured the hepatic secretion of very-low-density lipoprotein apolipoprotein B-100 (VLDL apoB) using a stable isotope gas-chromatography mass-spectrometry method in six patients with non-insulin-dependent diabetes mellitus (NIDDM) (four males, two females, age 57.5+2.2years (mean + SEM), weight88.2 + 5.5 kg, glycated haemoglobin (HbA1) 8.5 _+ 0.5 %, plasma total cholesterol concentration 5.7 + 0.5 mmol/1, triglyceride 3.8 + 0.9 mmol/1, high-density lipoprotein (HDL) cholesterol 1.0 + 0.1 mmol/1) and six no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
49
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 37 publications
(63 reference statements)
6
49
1
1
Order By: Relevance
“…These previous observations all would support the prediction that type 2 diabetes is associated with decreased MTP gene expression in the liver. This seems to contrast with the findings of increased hepatic lipoprotein secretion in individuals with type 2 diabetes who are both hyperinsulinemic and hyperglycemic (21)(22)(23). These observations could also reflect that other factors, e.g., lipid availability in hepatocytes, are more important than MTP levels in determining lipoprotein secretion rates from the liver of individuals with diabetes or that MTP gene expression might be differently regulated in vivo than in cultured liver cells.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…These previous observations all would support the prediction that type 2 diabetes is associated with decreased MTP gene expression in the liver. This seems to contrast with the findings of increased hepatic lipoprotein secretion in individuals with type 2 diabetes who are both hyperinsulinemic and hyperglycemic (21)(22)(23). These observations could also reflect that other factors, e.g., lipid availability in hepatocytes, are more important than MTP levels in determining lipoprotein secretion rates from the liver of individuals with diabetes or that MTP gene expression might be differently regulated in vivo than in cultured liver cells.…”
contrasting
confidence: 57%
“…These in vitro observations suggest that hepatic MTP gene expression might be decreased in individuals with hyperinsulinemic (type 2) diabetes. However, several metabolic studies have shown that individuals with type 2 diabetes display increased hepatic production of VLDL (21,24,34). The principal aim of the present study was to determine the effect of obesity-associated diabetes in mice on hepatic MTP gene expression, microsomal triglyceride transfer activity, and secretion of triglyceride-rich lipoproteins.…”
Section: Discussionmentioning
confidence: 93%
“…12,13 On the other hand, chronic hyperinsulinemia also has been associated with increased apoB-100 synthesis. 37 Differences in study conditions and methodologies make direct comparisons between remote studies difficult. Insulin levels were significantly greater in our NASH subjects than in either obese or lean controls.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with insulin resistance and diabetes are hyperinsulinemic and are resistant to the antilipolytic effect of insulin in peripheral tissues (15,16). Furthermore, hyperinsulinemic and insulin-resistant states are associated with VLDL oversecretion (17)(18)(19)(20)(21), which is the main cause of the elevation of TG-rich lipoproteins (TRLs) seen in these patients. The elevation in TRLs, in turn, contributes to their increased risk of cardiovascular disease (22,23).…”
mentioning
confidence: 99%